2017
DOI: 10.1089/vbz.2017.2145
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Multidrug-Resistant Community-Acquired Methicillin-Resistant Staphylococcus aureus at the Largest Veterinary Teaching Hospital in Costa Rica

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen associated with severe infections in companion animals present in the community, and it is diagnosed in animals admitted to veterinary hospitals. However, reports that describe the circulation of MRSA in animal populations and veterinary settings in Latin America are scarce. Therefore, the objective of this study was to determine the prevalence and investigate the molecular epidemiology of MRSA in the environment of the largest veterinary teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 54 publications
1
26
0
2
Order By: Relevance
“…A similar trend of CA-MRSA being MDR has been observed elsewhere especially in Europe, Asia and the Americas [4346]. Case in point is a study from a large veterinary teaching hospital in Costa Rica where nearly all CA-MRSA isolates investigated were MDR and carried SCC mec type IV [44].…”
Section: Discussionsupporting
confidence: 54%
“…A similar trend of CA-MRSA being MDR has been observed elsewhere especially in Europe, Asia and the Americas [4346]. Case in point is a study from a large veterinary teaching hospital in Costa Rica where nearly all CA-MRSA isolates investigated were MDR and carried SCC mec type IV [44].…”
Section: Discussionsupporting
confidence: 54%
“…Considering studies about HAIs in human medicine, the potential for similar problems in veterinary medicine exists. Various bacteria were found on surfaces and employees in different studies in veterinary clinics, and the potential for cross‐contamination was found in previous reports …”
Section: Discussionmentioning
confidence: 76%
“…Antimicrobial resistance in companion animals is of public health importance because of the close contact between pets and their owners, which can facilitate the transmission of resistant bacteria [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The trend towards intensive medical care of dogs and cats fosters hospitalization and nosocomial infections [ 10 , 11 , 12 , 13 ] and has led to a growing number of geriatric and immunosuppressed animal patients that are highly susceptible to infections, including those with antimicrobial resistant microorganisms (ARM). Antimicrobial use, which is discussed as one of the main drivers of resistance development, is common in companion animal medicine, including the use of highest priority critically important antimicrobials and even antibiotics of last resort, such as carbapenems, are administered in some instances [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%